Assessment of cobalt–free ferrite–based perovskite Ln0.5Sr0.5Fe0.9Mo0.1O3–δ (Ln = lanthanide) as cathodes for IT-SOFCs. Issue 4 (April 2021) - Wu, Ming; Cai, Hongdong; Jin, Fangjun; Sun, Ning; Xu, Jingsheng; Zhang, Leilei; Han, Xu; Wang, Shibo; Su, Xiaogang; Long, Wen; Wang, Li; Zhang, Lei
Highlights: Only Ln = La, Pr and Nd could be co–doped with Mo into SrFeO3–δ host lattice. LnSFM (Ln = La, Pr and Nd) were assessed as cathode materials for IT–SOFCs. TECs of the LnSFM (Ln = La, Pr and Nd) were 12.9–13.5 × 10 –6  K –1 at 300–900 °C. The LaSFM cathode showed the optimal conductivity and electrochemical performance. Good stability for the single cells with LnSFM cathodes was determined. Abstract: Cobalt–free perovskites Ln0.5 Sr0.5 Fe0.9 Mo0.1 O3–δ (Ln = lanthanide; LnSFM) were prepared via a sol–gel process. Pure rhombohedral phases were still not obtained for the samples (Ln = Sm and Gd) even sintered at 1300 °C. Thus, only the LaSFM, PrSFM and NdSFM compositions were assessed as IT–SOFC cathodes in terms of their thermal, electrical and electrochemical properties. Thermal expansion of the LnSFM was well compatible with that of Sm0.2 Ce0.8 O1.9 (SDC) electrolyte. Both conductivity and electrochemical performances of the LnSFM followed the same sequence of La > Nd > Pr. For the LaSFM, NdSFM and PrSFM cathodes, peak conductivities reached 73, 63 and 59 S·cm –1 at 650 °C; polarization resistances attained 0.211, 0.446 and 0.469 Ω·cm 2 at 700 °C; peak power densities of the LnSFM cells with 300–μm–thick SDC electrolyte achieved 269, 261 and 233 mW·cm –2 at 700 °C without cell degradation for operating 100 h. By comprehensive comparison, the LaSFM is assessed as a preferred cobalt–free ceramic cathode for IT–SOFC.